The Design of a Noise Detection Automatisation Tool in Library – Based on Internet of Things - Dhiya, Dhiya Alfiyyah Ansar; Yuyun; Taufik, Imran (Inspiration: Jurnal Teknologi Informasi dan Komunikasi, 2022)
The development of the times and technology produces innovations that facilitate human activities, one of which is for librarians to control and maintain library rooms. This study aimed to implement a noise detection automation tool and a sound monitoring system based on the Arduino nano 33 BLE sense microcontroller in a library room. The Arduino processed the data from the sound sensor through the Edge Impulse platform. Suppose a sound with a value exceeds 0.6 and takes more than 10 seconds. In that case, the warning "QUIET, PLEASE!" will be displayed, and a sound warning will also be issued via a buzzer. The sound warning can be monitored to turn on and off the buzzer through the application. When the librarian wants to turn off the buzzer, they can click the button to turn off the speaker; on the other hand, if they want to keep the buzzer on, they can click the button to turn on the speaker.